Determination characteristic of voltage sags on combination of three phase induction and synchronous motors / Alia Nabila Abd Aziz - Abd Aziz, Alia Nabila (2014)
This thesis focuses to the characteristics of voltage sags occur due to the combination of three phase induction and synchronous motors. Voltage sag basically described in magnitudes (voltage and current) and duration of time. These factors are important to determine the characteristics of three phase induction motor and synchronous motor. The study of voltage sag during starting motor is essential to minimize the risk of interruption. This project was performed with laboratory experimental work in order to obtain the corresponding waveform.